Effectiveness and Safety of Interferon-Free Direct-Acting Antiviral Hepatitis C Virus Therapy in HIV/Hepatitis C Virus Coinfected Individuals: Results From a Pan-European Study. (1st February 2021) - Amele, Sarah; Peters, Lars; Rodger, Alison; Lundgren, Jens; Rockstroh, Jurgen; Matulionyte, Raimonda; Leen, Clifford; Jabłonowska, Elzbieta; Østergaard, Lars; Bhagani, Sanjay; Sarcletti, Mario; Clarke, Amanda; et al.
Abstract : Objectives: To investigate the effectiveness, safety, and reasons for premature discontinuation of direct-acting antivirals (DAAs) in a diverse population of HIV/hepatitis C virus (HCV) coinfected individuals in Europe. Methods: All HIV/HCV coinfected individuals in the EuroSIDA study that started interferon free DAA treatment between January 6, 2014, and January 3, 2018, with ≥12 weeks of follow-up after treatment stop were included in this analysis. Sustained virological response (SVR) was defined as a negative HCV-RNA result ≥12 weeks after stopping treatment (SVR12). Logistic regression was used to explore factors associated with SVR12. Results: 1042 individuals started interferon-free DAA treatment after 1/6/2014 and were included, 862 (82.2%) had a known response to treatment, and 789 [91.5%, 95% confidence interval (CI): 89.7 to 93.4] of which achieved SVR12. There were no differences in SVR12 across regions of Europe ( P = 0.84). After adjustment, the odds of achieving SVR12 was lower in individuals that received sofosbuvir/simeprevir ± ribavirin (RBV) [adjusted odds ratio 0.21 (95% CI: 0.08 to 0.53)] or ombitasvir/paritaprevir/dasabuvir ± RBV [adjusted odds ratio 0.46 (95% CI: 0.22 to 1.00)] compared with sofosbuvir/ledipasvir ± RBV. Forty-three (4.6%) individuals had one or more components of their HCV regimen stopped early, most commonly because of toxicity (n = 14); of these 14, 11 were treated with ribavirin. Increased bilirubin was the most common grade 3 or 4 laboratory adverse event (n = 15.3%) and was related to treatment with atazanavir and ribavirin. Conclusions: Our findings from real-world data on HIV/HCV coinfected individuals across Europe show DAA treatment is well tolerated and that high rates of SVR12 can be achieved in all regions of Europe.